Majlis Bandaraya Johor Bahru / Muhammad Nabil Ashraffi Jamalludin - Jamalludin, Muhammad Nabil Ashraffi (Faculty of Business and Management, 2025)
During my six-month internship in the Licensing Department at Majlis Bandaraya Johor Bahru (MBJB), I had the opportunity to gain valuable insights into municipal licensing operations and contribute meaningfully to the department’s functions. This experience enhanced my understanding of local government processes while enabling me to develop skills relevant to licensing administration and public service. As an intern, I was there for eligibility application processing and ensured adherence with various municipal regulations, accurate record-keeping in the department, and supervising different levels of verification of documents and standards. Luckily, I worked with peers and supervisors effectively because of participation in community outreach programs that serve as a guide for applicants while doing his/her licensing process. It was purely about the inquiries and resolutions of all issues pertaining to licensing. A person under this internship would have to master both verbal and written communication skills along with attention to detail, as the information most surely has to be accurate while remaining compliant with municipal regulations. Colleagues got involved in designing methods to ease workflow improvement and amendments to internal process updating that would end up trimming down the application processing turnaround time. Learning the ropes in the business was priceless, as I now understand just how critical licensing is to an orderly business environment and compliance in the community. In addition, my problem-solving skills were enhanced by this experience, and it will help me greatly in my future career. In short, my stay at the Licensing Department of MBJB was certainly informative and rewarding. I've learned many exciting things, inculcated skills in a practical context of use and purpose for my career goals, along with a culture to value the pivotal role of local government in community-based development.